Studies on Anoestrum in Crossbred Cattle - Vijayakrishnapillai G P (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1980)
The object of the study was to assess the incidence of anoestrum among crossbred cattle of Kerala and to find out the possible etiological factors so as to evolve suitable therapeutic measures for the same. For this, 184 crossbred cows and 76 crossbred heifers above 18 months of age maintained in the livestock farms attached to the Kerala Agricultural University and 401 crossbred cows and heifers presented for treatment at various infertility camps in the State were utilised. The incidence of anoestrum was assessed from the breeding history and detailed gynaecoclinical examinations. The nutritional status of the animals was determined by haematological examinations. The anoestrous animals showing nutritional deficiency were treated with Fertimin brand of mineral mixture and those showing normal nutritional status were treated with ‘Fertivet’. Among the farm animals, 28.3 per cent of cows 28.4 per cent of heifers were in apparent anoestrum though true anoestrum was observed only in 17.4 per cent of cows and 22.4 per cent of heifers. The other cases of apparent anoestrum were due to silent oestrum (3 to 15 per cent), cystic ovaries (0.5 to 1.3 per cent) and hypoplasia of ovaries (1.3 per cent). Similarly among the animals brought for treatment at various infertility camps, true anoestrum was observed only in 28.2 per cent though 49.9 per cent were reported to be anoestrous. The other cases were early pregnancy (2.7 per cent), cycling (7.7 per cent), cystic ovaries (0.2 per cent), underdeveloped genitalia, (9 per cent) ovarian hypoplasia (0.2 per cent) and in heat (1.7 per cent) Wide Ca. P ratio (2.69 and 2.46) and subnormal copper level (88.32 g/dl and 91.07 g/dl) were detected in 46.6 per cent of cows and 54.65 per cent of heifers respectively in true anoestrum. ‘Fertivet’ was capable of inducing ovulatory oestrum in 100 per cent of cows and 89.47 per cent of heifers in true anoestrum due to non nutritional causes within a period of 5.73 and 5.43 days respectively, while only 33.3 per cent of cows and 30 per cent of heifers in the control group came in heat; the variations being highly significant. Similarly, the conception rate in the treated groups was 66.6 per cent for cows and 42.11 per cent for heifers, while only one cow from the control group conceived, the variation in both the cases being significant. Treatment with ‘Fertimin could induce ovulatory oestrum in 91.67 per cent of cows and 78.26 per cent of heifers within a mean period of 38.8 and 27.77 days respectively, while the response in the control groups were only 11.1 per cent for cows and 25 per cent for heifers respectively, the difference being highly significant in both the cases. Significant variations were observed in conception rate between experimental and control groups, the values being 50 per cent for cows and 43.48 per cent for heifers in the experimental group. None of the animals in control groups conceived.